THE TRANSFORMATION OF RELIGION VALUES AS LOCAL WISDOM IN PANJI SOCIETY - Kokom Komalasari, Suzana Paranita Dadang Supardan (Department of Civic Education, 2015)
This study originated from the researchers’ anxiety over the weakening of local culture. The religious aspect became the main focus because in reality Indonesian society religiousness always transforms from primitive belief into faith in religion. The case in this study is the transformation of religious values as the local wisdom in Panji society, and this is done by looking at the religion values in local culture of Panji and as such it becomes ethnopedagogy review in learning. The aim of the study is to know how the transformation of religion values as local wisdom in Panji society. The method used in this study is ethnography with qualitative approach. Data is collected via observation, interview, and documentation. Data is analyzed by reducing it first, then it is reviewed and conclusion is deducted. The result concludes that Panji society understands religious values as local wisdom through the system called as Nuju Jerami. The faith in God in Panji society has not yet been implemented in formal education, though the religious values in Nuju Jerami content actually is possible to be integrated into formal lesson. The pull and push happened when religion and culture become an integrated part. It is hoped that based on the result of this research, these local wisdom values can be taught as local content in form of formal lesson in schools, be it primary school or secondary school.Keyword: Transformation, Religious, Local Wisdom, Panji society